MAIN APPROACHES TO BUSINESS DEVELOPMENT STRATEGY FORMATION - D. B. Smirnov (Модернизация, инновация, развитие)
Article tasks: defi ne main approaches to business development strategy formation. Methodology: methodological basis includes systemic, replication and dialectic general scientifi c approaches. Results: it is established that the activity approach as a leading methodology of strategy development assumes correlation between the activity category and the concepts: needs, interests, incentives, goals, refl ection (evaluation), and self-development. Systemic approach assumes to consider strategy as a system having a defi nite structure and interconnections within the system components. Conclusions/relevance: for Russian businesses the main goal in the management system is not a prompt response to current environmental changes, but formation of a strategic vision of the business’ future, elaboration of a fl exible and viable development strategy, to foresee tactical and strategic threats for the business activity, to remove them timely, as well as to use strategic management ideas in practice for sustainable growth.